Undiagnosed SARS-CoV-2 infection and outcome in patients with acute MI and no COVID-19 symptoms. Issue 1 (2nd April 2021) - Akhtar, Zubair; Chowdhury, Fahmida; Aleem, Mohammad Abdul; Ghosh, Probir Kumar; Rahman, Mahmudur; Rahman, Mustafizur; Hossain, Mohammad Enayet; Sumiya, Mariya Kibtiya; Islam, A K M Monwarul; Uddin, Mir Jamal; MacIntyre, C Raina; Cajander, Sara; et al.
Abstract : Objective: We aimed to determine the prevalence and outcome of occult infection with SARS-CoV-2 and influenza in patients presenting with myocardial infarction (MI) without COVID-19 symptoms. Methods: We conducted an observational study from 28 June to 11 August 2020, enrolling patients admitted to the National Institute of Cardiovascular Disease Hospital, Dhaka, Bangladesh, with ST-segment elevation MI (STEMI) or non-ST-segment elevation MI who did not meet WHO criteria for suspected COVID-19. Samples were collected by nasopharyngeal swab to test for SARS-CoV-2 and influenza virus by real-time reverse transcriptase PCR. We followed up patients at 3 months (13 weeks) postadmission to record adverse cardiovascular outcomes: all-cause death, new MI, heart failure and new percutaneous coronary intervention or stent thrombosis. Survival analysis was performed using the Kaplan-Meier method. Results: We enrolled 280 patients with MI, 79% male, mean age 54.5±11.8 years, 140 of whom were diagnosed with STEMI. We found 36 (13%) to be infected with SARS-CoV-2 and 1 with influenza. There was no significant difference between mortality rate observed among SARS-CoV-2 infected patients compared with non-infected (5 (14%) vs 26 (11%); p=0.564). A numerically shorter median time to a recurrent cardiovascular event was recorded among SARS-CoV-2 infected compared with non-infected patients (21 days, IQR: 8–46 vs 27 days, IQR: 7–44; p=0.378). Conclusion: We found a substantial rate of occult SARS-CoV-2 infection in the studied cohort, suggesting SARS-CoV-2 may precipitate MI. Asymptomatic patients with COVID-19 admitted with MI may contribute to disease transmission and warrants widespread testing of hospital admissions.